PENGARUH UKURAN PERUSAHAAN, PROFITABILITAS, LEVERAGE, LIKUIDITAS TERHADAP TAX AVOIDANCE PADA PERUSAHAAN SUB SEKTOR OTOMOTIF YANG TERDAFTAR DI BEI PERIODE 2014-2019 - Silverian Utomo Saputro; Siti Nurlaela; Riana Rachmawati Dewi (Jurnal Akuntansi dan Pajak, 2021)
The research objective was to determine the effect of company size, profitability, leverage, liquidity on tax avoidance in automotive sub-sector manufacturing companies listed on the Indonesian stock exchange for the 2014-2019 period. The population in this study consisted of 13 companies using purposive sampling technique to determine the samples in order to obtain 9 companies that met the criteria. Financial data in this study were obtained through the IDX web and multiple linear regression analysis methods using SPSS 25 software. The T test results showed that company size, profitability, liquidity had no effect on tax avoidance. While the leverage variable has an effect on tax avoidance. The results of the F test show that simultaneously all independent variables have an effect on tax avoidance. Keywords: company size, profitability, leverage, liquidity, tax avoidance